1999
DOI: 10.1038/17755
|View full text |Cite
|
Sign up to set email alerts
|

Aharonov–Bohm oscillations in carbon nanotubes

Abstract: When electrons pass through a cylindrical electrical conductor aligned in a magnetic ®eld, their wave-like nature manifests itself as a periodic oscillation in the electrical resistance as a function of the enclosed magnetic¯ux 1 . This phenomenon re¯ects the dependence of the phase of the electron wave on the magnetic ®eld, known as the Aharonov±Bohm effect 2 , which causes a phase difference, and hence interference, between partial waves encircling the conductor in opposite directions. Such oscillations have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
486
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 774 publications
(522 citation statements)
references
References 24 publications
20
486
1
2
Order By: Relevance
“…Note that the AB and AAS effects can be observed in non-topological insulator material also if the electron transport in investigated system maintains the quantum coherency which gives rise to conductance oscillations. The earlier work on Bismuth nanowires [24], multiwall carbon nanotube [25], Au nanorings [26], magnesium film evaporated onto a quartz filament [27], graphene ring [28] and Dirac semimetal nanowires [29] have shown quantum interference of surface states indicating the AB oscillations. We assume these periodic oscillations could be coming from AB effects and gallium doping and or material deformation also affecting oscillation period and phase coherence length of the electrons.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the AB and AAS effects can be observed in non-topological insulator material also if the electron transport in investigated system maintains the quantum coherency which gives rise to conductance oscillations. The earlier work on Bismuth nanowires [24], multiwall carbon nanotube [25], Au nanorings [26], magnesium film evaporated onto a quartz filament [27], graphene ring [28] and Dirac semimetal nanowires [29] have shown quantum interference of surface states indicating the AB oscillations. We assume these periodic oscillations could be coming from AB effects and gallium doping and or material deformation also affecting oscillation period and phase coherence length of the electrons.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the topological nature of the 1D surface sub-bands can be observed via the behaviour of the AB oscillation maxima and minima as a function of F/F 0 : for the lowest-energy mode (at the Dirac point), a minimum in conductance should occur at F/F 0 ¼ 0, while a maximum in conductance should occur at F/F 0 ¼ 0.5, as the non-degenerate gapless mode reappears 10,11 . This mode contains massless Dirac-like excitations that follow a 1D linear energy-momentum dispersion, and is not observed in non-topological systems [7][8][9]12 .…”
mentioning
confidence: 95%
“…When a magnetic field (B) is applied along the nanowire axis, the surface electrons encircling the wire pick up a phase of 2pF/F 0 , where F ¼ BS is the magnetic flux through cross-sectional area S and F 0 ¼ h/e is the magnetic flux quantum, where h is Planck's constant and e the electron charge. The energymomentum relation is, thus, periodic in F/F 0 , leading to h/e Aharonov-Bohm (AB) oscillations [7][8][9] . In topological insulators, the spin-momentum locking causes carriers encircling the wire to also acquire a p Berry phase, which is predicted to open up a gap in the lowest-energy one-dimensional (1D) surface sub-band.…”
mentioning
confidence: 99%
“…The theory provides a good fitting of the experimental results. Carbon nanotubes connected to metallic electrodes allow to study many different regimes in mesoscopic electron transport exhibiting either ballistic or diffusive behavior [1,2]; Luttinger liquid features [3], etc. Several experiments [4] have demonstrated that carbon nanotubes weakly coupled to normal leads can also exhibit Coulomb blockade and Kondo effect, i.e.…”
mentioning
confidence: 99%